Rice Crop Manager - Myanmar - CGIAR Research Program on Rice (2019)
Focus group discussions and RCM questionnaire have been developed. The RCM prototype was developed in 2019 and shared with the Myanmar Department of Agriculture. In addition, the user interface was updated to include feedback from target users so that it was more user-friendly and understandable.